Fiscal incidence when both individual welfare and family structure matter: The case of subsidization of home-care for the elderly - Haizhen Mou; Stanley L. Winer (Center for Economic Studies and ifo Institute (CESifo), 2012)
How should we construct incidence indexes for children and parents in the case of public subsidies for home-care of the elderly? What is the nature of a fiscal incidence index on a budgetary basis versus a theoretically more satisfactory index that is welfare-based? Can we find budgetary based measures that will serve as a proxy for incidence in welfare terms? Does the structure of the family including the altruism of children affect incidence indexes? How should fiscal shifting of the subsidy for home care paid to the parents be defined, in budgetary or in welfare terms, and what does simulation tell us about the distribution of benefits between the generations? We address these issues analytically and with simulation (using data from the Medical Expenditure Panel Survey) in this contribution to the study of fiscal incidence. The definition of welfare incidence, the comparison of welfare-based incidence with budgetary incidence for non-cooperative and cooperative families, and the calculation of the shifting of program benefits between family members, some of whom may be altruistic, are key issues in the analysis. The integration of individual welfare, family structure and benefit shifting provides a new perspective on the fiscal incidence of home care programs.
Keywords: H22; I18; D13; 330; home care of the elderly; price-subsidy; fiscal incidence index; non-cooperative family; cooperative family; income pooling; altruism; benefit shifting; Medical Expenditure Panel Survey; Medicaid; simulation; Pflegedienst; Subvention; Budgetinzidenz; Familiensoziologie; Altruismus; Wohlfahrtseffekt; Index; Simulation; USA